EARLY DETECTION AND TREATMENT OF HYPERTENSION WITH COCONUT WATER - Masroni Masroni (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2022)
The BATARA village (Read Taman Rimba) is located on the edge of the forest in the Papring area. This village is about 15 kilometres from downtown Banyuwangi, and is located at an altitude of 1000 meters above sea level. The location and infrastructure that are still inadequate will have an impact on education and health services because of the distance from health facilities, so that it is possible that it will be fatal if there is a complication of hypertension such as stroke or other diseases if not handled immediately. To train the community's independence in health problems, by providing Health Education regarding early detection of hypertension and treatment with coconut water and how to carry out blood pressure measurements to prevent heart, kidney, brain and other diseases. The implementation of this service includes 3 stages, the first stage; socialization of activities to be carried out, identification of needs, identification of existing potentials and weaknesses and organizing activities, second stage; the implementation stage of activities in order to improve competence in a peer group and comprehensive manner, while the third stage, monitoring and evaluation in order to achieve the success of the activity. The results of this Community Service Activity, the residents of BATARA village are able to prevent hypertension with coconut water and are able to carry out blood pressure measurements independently in order to prevent hypertension and its complications. Keywords: Detection, early treatment, hypertension, coconut water,